2012
DOI: 10.1002/ejsp.1924
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of gender‐fair language: How feminine job titles influence the evaluation of female applicants

Abstract: In many languages, feminization has been used as a strategy to make language more gender‐fair, because masculine terms, even in a generic function, exhibit a male bias. Up to date, little is known about possible side effects of this language use, for example, in personnel selection. In three studies, conducted in Polish, we analyzed how a female applicant was evaluated in a recruitment process, depending on whether she was introduced with a feminine or masculine job title. To avoid influences from existing occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 68 publications
5
57
0
4
Order By: Relevance
“…Indirect support for the assumption that gender-fair language might affect perceptions of warmth and competence comes from research comparing the impact of the masculine singular vs. the feminine singular form for job titles on evaluations of those jobs and their suitability for female applicants (Merkel et al, 2012; Formanowicz et al, 2013; Budziszewska et al, 2014). For example Formanowicz et al (2013) demonstrated with both invented (Studies 1–2) and existing (Study 3) job titles that female applicants described with a feminine job title were evaluated as being less competent than applicants described with a masculine job title.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect support for the assumption that gender-fair language might affect perceptions of warmth and competence comes from research comparing the impact of the masculine singular vs. the feminine singular form for job titles on evaluations of those jobs and their suitability for female applicants (Merkel et al, 2012; Formanowicz et al, 2013; Budziszewska et al, 2014). For example Formanowicz et al (2013) demonstrated with both invented (Studies 1–2) and existing (Study 3) job titles that female applicants described with a feminine job title were evaluated as being less competent than applicants described with a masculine job title.…”
Section: Introductionmentioning
confidence: 99%
“…For example Formanowicz et al (2013) demonstrated with both invented (Studies 1–2) and existing (Study 3) job titles that female applicants described with a feminine job title were evaluated as being less competent than applicants described with a masculine job title. While job titles in the feminine form lead to some devaluation of competence, women are often evaluated more favorably than men on warmth (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In languages where gender-fair language was or is still a matter of debate (English in the 1990s: McConnell and Fazio, 1996; Polish and Italian in the first two decades of the twenty-first century: Mucchi-Faina, 2005; Merkel et al, 2012; Formanowicz et al, 2013), the use of feminine job titles for individual women was found to reduce women's professional credibility and evaluation, suggesting that gender-fair language and other regulations for political correctness may be counter productive. However, this conclusion may be premature as we still do not know the popular reaction to politically correct language after it has been implemented for a longer time.…”
Section: Introductionmentioning
confidence: 99%
“… 8 In Study 2 we have used a scale that was previously used in Poland (Formanowicz et al, 2013). However, for the German language we referred to the related scale for which the translation was available for us.…”
mentioning
confidence: 99%
“…), on prospective employers (Formanowicz et al. ), and on the public perceptions in general (Wood‐Nartker et al. ).…”
Section: Literature Reviewmentioning
confidence: 99%